Chemokines as potential biomarkers for predicting the course of COVID-19 – a review of the literature - Wolszczak-Biedrzycka, Blanka; Cieślikiewicz, Beata; Studniarz, Filip; Dąbrowski, Łukasz; Fąs, Mateusz; Matyszkiewicz–Suchodolska, Krystyna; Harasimowicz, Monika; Dorf, Justyna (Frontiers in Immunology, 2025)
Since the beginning of the COVID-19 pandemic, research has been ongoing to find the best diagnostic parameters to identify patients with a high risk of severe infection. Numerous studies have examined chemokine biomarkers in COVID-19 as a biomarker for high risk patients. The four main structural proteins of the SARS-CoV-2, spike protein, membrane protein, envelope protein and nucleocapsid protein enable the virus to penetrate host cells and stimulate the immune system. SARS-CoV-2 enters host cells via ACE2 in upper respiratory tract the virus entries by binding to the spike protein. Uncontrolled activation and enhancement of the immune response leads to massive release of cytokines and chemokines known as cytokine storm (CS). Chemokines are described as important cytokines in COVID-19 with a potential role as prognostic factor particularly for the severity of the infection and the risk of death from complications, to identify high-risk patients. Our review contains chemokines (CCL2, CCL3, CCL5, CXCL8, CXCL10), which level is significantly higher in patients with COVID-19 infection vs control individuals.